Flexible retirement and optimal taxation - Abdoulaye E. N'Diaye (Federal Reserve Bank of Chicago, 2018)
This paper studies optimal insurance against private idiosyncratic shocks in a life-cycle model with intensive labor supply and endogenous retirement. In this environment, the optimal labor tax is hump-shaped in age: insurance benefits of taxation push for increasing-in-age taxes while rising labor supply elasticities and optimal late retirement of highly productive workers push for lowering taxes for old workers. In calibrated numerical simulations, the optimum achieves sizable welfare gains that age-dependent taxes do not deliver under the status quo U.S. Social Security. Nevertheless, an optimal combination of age-dependent linear taxes with increasing-in-age retirement benefits generates welfare gains close to optimal.
Keywords: H21; H55; J26; 330; Retirement; Optimal Taxation; Social Security; Continuous-Time; Optimal Stopping